Gangguan Ginjal Akut akibat Keracunan Jengkol - Idha Yulfiwanti; Aumas Pabuti; Fitrisia Amelin; Ronaldi Noor (Faculty of Medicine, Universitas Andalas, 2023)
Jengkolic acid intoxication is one of the causes of acute kidney injury in children. This case report discusses the diagnosis and management of jenkol intoxication in children. We reported a 12-year-old boy with painful urination accompanied by low back pain and urine was initially whitish-colored sand then turned red-colored urine accompanied by reduced urine volume after consuming jengkol. The patient was diagnosed with acute kidney injury due to jenkolic acid intoxication, urinary tract infection, and bilateral hydronephrosis with initial conditions of oliguria, elevated urea, the impression of an estimated glomerular filtration rate (GFR) was stage failure, and planned emergency hemodialysis. The patient was managed with bicarbonate sodium and other symptomatic therapy. During monitoring of patients with increased urine output, decreased ureum and increased estimated GFR, hemodialysis was not performed. The patient was treated for 6 days and recommended for control at the pediatric clinic.